Evaluation of Futsal Training Program in North Sumatera - Akmal, Ahmad Zhafri; Sulaiman, Sulaiman; Hartono, Mugiyo (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The objectives of this study are context, including background, vision, mission, and the goal of the training program; input, including the human resources, facilities and infrastructure properness, and the financial sources of the training program of North Sumatera futsal team; process, including the implementation of training program, coaches’ performance, transportation and coordination among elements; product, including the achievement of North Sumatera futsal. The results of this study are context teaches the vision, mission, and goals of North Sumatera futsal, the input of North Sumatera Futsal Association has quality human resources, excellent facilities, and infrastructure, and limited financial sources, the process of the training program is the authority of the coach and coaches’ assistant. The athlete recruitment is included in the coaches’ authority; however, it considers the committee’s suggestion during the recruitment. Both transportation and coordination are good in North Sumatera Futsal Association, the product of the futsal training program is an achievement, the futsal achievement in North Sumatera is already good, but less stable in maintaining the winner position in 2012-2017. This study concludes that the context, input, and process aspects are already excellent, while the product of North Sumatera futsal has gained good achievement as North Sumatera futsal team often participates in futsal competition in Indonesia. However, the team is not stable to maintain the winner position.